Pierre Hadot (1922”‘2010), In memoriam - Hoffmann, Philippe (Revista Archai, 2016)
This paper provides a bio”‘bibliographical survey of the life and works of Pierre Hadot, following the main steps of his academic career (at the CNRS, the École pratique des hautes études and the Collège de France), and the various periods of his research: Latin Patristic (Ambrosius and Augustine), History of Neoplatonism (Porphyry, Marius Victorinus, then Plotinus), Stoicism (Epictetus and Marcus Aurelius), general interpretation of the phenomenon of Ancient Philosophy as a way of life, with a special focus on the “Spiritual Exercises”. Keywords: Ancient Philosophy, Late Antiquity, Stoicism, Neoplatonism, Spiritual Exercises.